Salinity effects on oocytes, fertilized egg density and the reproduction rate of the tilapia Sarotherodon melanotheron heudelotii (Duméril, 1859) in natural and controlled environments - Moussa Guèye; Mbaye Tine; Justin Kantoussan (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
The effects of salinity on the variation of egg and oocyte densities and reproduction rate in the euryhaline tilapia Sarotherodon melanotheron heudelotii was investigated under natural and controlled conditions. The study was conducted on fish from a single population maintained under laboratory conditions for several generations. Fish were exposed to three different salinities conditions: freshwater (0 psu), seawater (35 psu) and hypersaline water (70 psu) while other environmental factors and feeding conditions were held constant. The wild population analyses were conducted on fish collected in environments with different salinities: Guiers lake (0 psu), Gambia estuary (21 psu), Hann Bay (35 psu) and Saloum estuary (54-130 psu). In both natural and controlled environments, the eggs and oocyte densities in freshwater and seawater are much higher than the density of water, which ensures a successful fertilization of eggs and therefore lead to a high reproduction. However in hypersaline condition, opposite results are obtained depending on the environment. In natural hypersaline conditions, the reproduction rate remains optimal despite the reduced oocyte density compared to the density of water. By contrast, in controlled hypersaline environment, the reduced egg density is accompanied with a low reproduction rate. These results suggest that under hypersaline conditions, the reduced oocyte density compared to that of water can prevent fertilization and reduce the reproduction rate. The high reproduction rate obtained in the hypersaline zone of the Saloum estuary in the wild suggests an adoption of a reproductive strategy consisting of a short migration of the spawners towards the oligohaline zones to ensure a successful reproduction.